Sonifying science: listening to cancer - Ihde, Don (Nursing philosophy, 2017)
As a long-time scholar of science and art practices, I look particularly at the role of tools and instruments which make these practices possible. I note that science, historically, has favoured visualist imaging, but art, particularly in performance modes, often uses acoustic imaging. Early modern science was dominantly optical in instrumentation, but uses of optics often preceded science use in early modern times. In late modern times, much more complex instrumentation often originated in the sciences, but artists frequently adapted to acoustic practices. Sonifying science, from imaging space phenomena to medical phenomena, is traced here, focusing upon medical sonification in detecting cancers.